1987
DOI: 10.1002/1097-0142(19870101)59:1<83::aid-cncr2820590119>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

The correlation of growth fractions with histologic grading and lymph node status in human mammary carcinoma

Abstract: The monoclonal antibody Ki-67 reacts with a human nuclear associated with cell proliferation that is expressed only in the G1, S, G2, and M phases of continuously cycling cells. This offers a simple opportunity to determine the growth fraction of tumors by immunostaining of fresh tissue. One hundred fifty-four invasive carcinomas of the breast were used in this study. The average number of Ki-67 positive cells was 15.3 +/- 10.1% (range, 1%-48%), whereas in 41 benign lesions of the breast only 4.4 +/- 2.6% (ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
23
0
1

Year Published

1989
1989
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(26 citation statements)
references
References 20 publications
2
23
0
1
Order By: Relevance
“…Several reports have now examined the binding of Ki67 in breast cancer specimens and have observed a significant relationship with the histological grade of malignancy and the mitotic activity of tumours (Barnard et al, 1987;Gerdes et al, 1984b;Lelle et al, 1987). This association has been confirmed in our series and extended to show, for the first time, that the binding of the Ki67 antibody also correlates with the early recurrence of breast cancer, specifically when large numbers of tumour cells immunostain (> 20% (Baisch & Gerdes, 1987) growth and then falls back to 5-10% at confluence (manuscript in preparation).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Several reports have now examined the binding of Ki67 in breast cancer specimens and have observed a significant relationship with the histological grade of malignancy and the mitotic activity of tumours (Barnard et al, 1987;Gerdes et al, 1984b;Lelle et al, 1987). This association has been confirmed in our series and extended to show, for the first time, that the binding of the Ki67 antibody also correlates with the early recurrence of breast cancer, specifically when large numbers of tumour cells immunostain (> 20% (Baisch & Gerdes, 1987) growth and then falls back to 5-10% at confluence (manuscript in preparation).…”
Section: Discussionsupporting
confidence: 87%
“…This result complements the study of Barnard et al (1987), but is at slight variance with the data of Lelle et al (1987), who suggested that the average number of Ki67 positive cells in breast tumours was slightly higher in (Cooke, 1982). Interestingly, using a bivariate analysis, Meyer et al (1983) suggested that the prognostic relevance of ER in predicting the course of the disease following mastectomy was largely dependent on its relationship to proliferative activity, a conclusion also reached by Nicholson et al (1984) examining the prognostic value of mitotic activity and ER.…”
Section: Discussionsupporting
confidence: 87%
“…[22][23][24][25] The majority of these studies considered breast lesions to be a homogeneous disease with respect to the cellular composition of the growth fraction. In contrast to this view, our previous results, [8][9][10][11][12] in line with findings of others, 26 indicated that different cell types are involved in the development and progression of benign proliferative breast diseases on the one hand and of premalignant and malignant breast diseases on the other hand.…”
Section: Discussionmentioning
confidence: 99%
“…Other workers have shown that the Ki67 LI is positively correlated with histological grade (Gerdes et al, 1986;McGurrin et al, 1987;Lelle et al, 1987;Barnard et al, 1987;Walker & Camplejohn, 1988;Raymond & Leong, 1989;Wrba et al, 1989) and negatively correlated with oestrogen receptor content determined both immunohistologically and biochemically Charpin et al, 1989;Bouzubar et al, 1989;Raymond & Leong, 1989;Wrba et al, 1989;Colley et al, 1989;Vollmer et al, 1989;Helin et al, 1989) and data obtained from our study are in agreement with these findings. Overall, the breast tumours in our study had a low mean Ki67 LI (7.0%) in comparison to other studies which report a range of mean Ki67 LI's from 7.2% to 22% (Wintzer et al, 1991).…”
Section: Discussionmentioning
confidence: 99%